Changes in co-therapies after initiation of disease-modifying anti-rheumatic drugs (DMARDs) therapy in patients with rheumatoid arthritis - Kawai, Vivian K. (2011)
OBJECTIVES: We hypothesized that initiation of a new disease modifying anti-rheumatic drug DMARD) for rheumatoid arthritis (RA) treatment would decrease use of corticosteroids, nonsteroidal anti-inflammatory drugs (NSAIDs) and narcotics. METHODS: Using administrative databases we assembled 4 retrospective cohorts of RA patients (1998-2005), and identified 5 groups initiating DMARD regimens: methotrexate with (new MTX) or without (first MTX) use of other non-biologic DMARDs in the previous year; new hydroxychloroquine and/or sulfasalazine (new HCQ/SSZ) and new leflunomide (new LEF), both with previous use of MTX; and new TNF-α antagonists (new anti-TNF). We compared within-person differences in any use of co-therapies (≥1 prescription) between the 6 months before and the 6-12 months after DMARD initiation. RESULTS: Among 32476 DMARD initiators, the prevalence of corticosteroids, NSAIDs and narcotics use increased by 15%, 5% and 6% respectively in the 6 months before initiation compared to the previous 6 months suggesting worsening of the disease. In the 6 to 12 months after initiation for most initiator groups, more patients stopped using corticosteroids and NSAIDs than started, with overall decreases of 8.9% [95%CI 8.4-9.4%] for corticosteroids and 12.9% [95%CI 12.3-13.4%] for NSAIDs. The proportion of narcotic users changed little (overall decrease of 2.5% [95%CI 1.9-3.0%]). CONCLUSIONS: Use of all three co-therapies increased in the 6 months before initiation of new DMARD regimens for RA. Use of corticosteroids and NSAIDs decreased modestly 6-12 months fter initiation, but there was only a very small decrease in narcotic use. These differential changes require further study.